Constructing a new leading indicator for unemployment from a survey among German employment agencies - Christian Hutter; Enzo Weber (Applied Economics, 2015)
The paper investigates the predictive power of a new survey implemented by the Federal Employment Agency (FEA) for forecasting German unemployment in the short run. Every month, the CEOs of the FEA's regional agencies are asked about their expectations of future labor market developments. We generate an aggregate unemployment leading indicator that exploits serial correlation in response behavior through identifying and adjusting temporarily unreliable predictions. We use out-of-sample tests suitable in nested model environments to compare forecasting performance of models including the new indicator to that of purely autoregressive benchmarks. For all investigated forecast horizons (1, 2, 3 and 6 months), test results show that models enhanced by the new leading indicator significantly outperform their benchmark counterparts. To compare our indicator to potential competitors we employ the model confidence set. Results reveal that models including the new indicator perform very well at the 10 percent level.
Keywords: C22; C52; C53; E24; 330; Survey Data; Forecast Evaluation; Nested Models; Model Confidence Set; Unemployment